2008
DOI: 10.1590/s0100-06832008000600013
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de uréia em misturas com sulfato de amônio ou com gesso na cultura de milho

Abstract: & Elias Nascentes Borges (5) RESUMOAspectos qualitativos e quantitativos devem ser considerados na adubação nitrogenada de cobertura na cultura de milho. Este estudo teve por objetivo avaliar, nos municípios de Votuporanga (SP) e Uberlândia (MG), o efeito de diferentes misturas de grânulos, contendo N e S, na produtividade de milho. Em um Argissolo Vermelho eutrófico A moderado textura arenosa (120 g kg -1 de argila) de Votuporanga, foram estimadas as perdas por volatilização de N-NH 3 , das misturas de grânul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…Ammonium sulphate and urea are the two most nitrogen sources used in Brazilian agriculture, possibly because they are less expensive and more readily available in the market (Barbosa Filho et al, 2005). The volatilization losses when using ammonium sulphate are not large; however, this source typically has a cost per unit of nitrogen far superior to urea (Lara Cabezas et al, 2008). in a fulfilled study of eight varieties of flaxseed, five planting dates and rates of 0 to 150 kg ha -1 , found that the first sowing date March 14, along with 100 and 150 kg ha -1 of nitrogen produced the highest yield and production components.…”
Section: Introductionmentioning
confidence: 99%
“…Ammonium sulphate and urea are the two most nitrogen sources used in Brazilian agriculture, possibly because they are less expensive and more readily available in the market (Barbosa Filho et al, 2005). The volatilization losses when using ammonium sulphate are not large; however, this source typically has a cost per unit of nitrogen far superior to urea (Lara Cabezas et al, 2008). in a fulfilled study of eight varieties of flaxseed, five planting dates and rates of 0 to 150 kg ha -1 , found that the first sowing date March 14, along with 100 and 150 kg ha -1 of nitrogen produced the highest yield and production components.…”
Section: Introductionmentioning
confidence: 99%
“…As perdas por volatilização quando se utiliza o sulfato de amônio não são grandes (LARA CABEZAS et al, 2008), porém, essa fonte normalmente apresenta um custo por unidade de N muito superior à uréia. Uma alternativa seria a proteção da partícula da uréia com produtos menos higroscópicos que permitam aplicá-la na superfície do solo, favorecendo sua penetração de forma controlada e estimulando o processo de hidrólise no interior do solo, reduzindo as perdas de N na forma de NH 3 (BONO et al, 2006).…”
Section: Introductionunclassified
“…However, ammonium sulfate was the N source that provided the highest leaf S concentrations, due to the high concentration of S per unit mass (24%) in the form of sulfate (SO 4 2− ), which is the main form absorbed by plants and does not require oxidation by Thiobacillus , which, in turn, is dependent on soil temperature and moisture conditions [ 83 ]. On the other hand, the sandy soil probably favored more intense leaching of SO 4 2− due to the few anionic adsorption sites, decreasing the contact with the root system and, consequently, absorption by the plant [ 84 ]. This mechanism explains the higher concentration of S in the leaves of corn grown in clayey soil, as described in Figure 6 f.…”
Section: Discussionmentioning
confidence: 99%